Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pone.0227551
|View full text |Cite
|
Sign up to set email alerts
|

The nitrate content of fresh and cooked vegetables and their health-related risks

Abstract: Background Vegetables are the most important source of nitrates in the human diet. During various processes in the body, nitrates are converted into nitrites, which causes various diseases, such as blue baby syndrome and cancer. This study aimed to determine the concentration of nitrates in several vegetable farms in Sanandaj city and to evaluate their health-related risks. Methods This descriptive cross-sectional study was conducted from October 2017 to July 2018. A total of 90 samples were taken from nine fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 28 publications
(38 reference statements)
0
38
0
Order By: Relevance
“…Considering that vegetables constitute the primary source of nitrate exposure in the human diet [ 24 ], its high content represents a critical anti-nutritional factor. Basil, like other leafy vegetables, accumulates nitrate in its tissues [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that vegetables constitute the primary source of nitrate exposure in the human diet [ 24 ], its high content represents a critical anti-nutritional factor. Basil, like other leafy vegetables, accumulates nitrate in its tissues [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrates (NO 3 − ) per se are relatively nontoxic compounds; yet, around 5-10% of ingested nitrates are converted to nitrites (NO 2 − ) in the gastrointestinal tract [7]. Nitrites are highly toxic compounds that can lead to many disorders in humans [7] including blue baby syndrome (methaemoglobinemia in infants) as well as other diseases [8,9]. For these reasons, the reduction of nitrate intake associated with vegetables consumption in the diet is strongly recommended [10].…”
Section: Introductionmentioning
confidence: 99%
“…Two reasons may justify it; the first is the lower consumption of boiled compared to the raw spinach (about 10% in daily intake by the gram, and about five times by serving intake per year) in the present study. Second, it is previously observed that nitrate and total polyphenolic content and antioxidant activity of some vegetables, including spinach, are reduced during the cooking process [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%